2008
DOI: 10.1103/physrevb.77.075307
|View full text |Cite
|
Sign up to set email alerts
|

Experimental studies of the fractional quantum Hall effect in the first excited Landau level

Abstract: We present a spectrum of experimental data on the fractional quantum Hall effect (FQHE) states in the first excited Landau level, obtained in an ultrahigh mobility twodimensional electron system (2DES) and at very low temperatures and report the following results: For the even-denominator FQHE states, the sample dependence of the ν=5/2 state clearly shows that disorder plays an important role in determining the energy gap at ν=5/2. For the developing ν=19/8 FQHE state the temperature dependence of the R xx min… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
117
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 155 publications
(127 citation statements)
references
References 62 publications
5
117
0
Order By: Relevance
“…Therefore, they may strongly overlap at these system sizes, thereby leading to a finite gap for finite-size systems [78]. Hence, the extrapolation to the thermodynamic limit might be a much more delicate procedure then previously appreciated and, in fact, could point to a potential reason for the long-noticed discrepancy between calculated energy gaps and experimentally measured gaps [2][3][4][5][6][7][8][9][10]12,[14][15][16][17][18][19][20][21][22][23].…”
Section: Energy Gapsmentioning
confidence: 98%
“…Therefore, they may strongly overlap at these system sizes, thereby leading to a finite gap for finite-size systems [78]. Hence, the extrapolation to the thermodynamic limit might be a much more delicate procedure then previously appreciated and, in fact, could point to a potential reason for the long-noticed discrepancy between calculated energy gaps and experimentally measured gaps [2][3][4][5][6][7][8][9][10]12,[14][15][16][17][18][19][20][21][22][23].…”
Section: Energy Gapsmentioning
confidence: 98%
“…This FQHS was discovered 1 and studied in depth in high quality two-dimensional electron gases (2DEGs) confined to GaAs/AlGaAs heterostructures . Other even denominator FQHSs in the GaAs/AlGaAs system develop at ν = 7/2 6,16,40,41 and ν = 2 + 3/8 [42][43][44] and possibly related FQHSs have been observed at even denominators in ZnO/MgZnO 45 and in bilayer graphene [46][47][48][49] . Since its discovery it was clear that, owing to the even denominator of the filling factor, the ν = 5/2 FQHS is not part of the sequence prescribed by the free composite fermion theory 50,51 .…”
Section: Introductionmentioning
confidence: 99%
“…Fg, 73.43.Qt, 73.63.Hs Interest in the even-denominator fractional quantum Hall (FQH) state at ν = 5/2 in the first excited Landau level continues to remain high over twenty years after its discovery [1]. Generally believed to be due to the p−wave pairing of composite fermions [2,3,4,5], the quasi-particle excitations of this state are thought to obey nonabelian statistics and thus may be relevant to faulttolerant, topological quantum computing schemes [6,7].To date, observations of even-denominator FQH states have been rare beyond the ν = 5/2 state in single-layer systems [8]. In particular, experimental evidence for a FQH state at ν = 1/2, the lowest Landau level counterpart of the ν = 5/2 state, does not exist, although previous theoretical work has suggested that it may form in thick two-dimensional electrons systems (2DES) [9].…”
mentioning
confidence: 99%